A Research on Status of Entrepreneurship and Startup in India - Mohd. Ashfaq Siddiqui (AG Volumes, 2022)
The Indian economy is undergoing a fundamental shift because to the rise of startups. India is a country that has a culture of entrepreneurship, an open economic environment, and a favourable population, all of which make it very conducive to entrepreneurial activity. Nevertheless, India’s startup industry has not yet achieved full maturity, and a significant number of firms fail while they are still in their early stages. Establishing mentorship ties with well-established businesses may contribute to the creation of mutual success and help India move toward a future that is more dynamic. The number of people starting their own businesses has increased considerably in India, and these new businesses are starting to have a big effect on the economy. New business registration has increased from 15,000 in the 1980s to roughly 100,000 in the 2010s, and this growth has been enabled by robust demographics as well as an open and commercial culture. The average age of an entrepreneur in India is just 28 years old, placing them among the youngest in the world. And new businesses are starting to extend their advantages beyond their conventional sites and into the economy of surrounding areas. Established business models are being challenged and replaced by new ones that are being created by startups. Across all sectors, new startup enterprises pose a challenge to the status quo of established businesses and conventional distribution methods. As a result of this, they have the potential to serve as agents of change and cooperation within India’s many business ecosystems.